Supporting Faculty, Staff, and Student-Parents though Cognitive, Emotional, and Behavioral Engagement - Beth Kania-Gosche; Kathryn Northcut (Academic Chairpersons Conference Proceedings, 2023)
Presenters will describe intentionally developed supports for faculty, staff, and students with children, an aspect of diversity and inclusion often overlooked. Participants will see specific examples of ongoing initiatives, along with a theory of engagement that articulates cognitive, behavioral, and emotional/personal aspects.
Keywords: faculty retention; faculty parents; motherscholar; faculty burnout; on campus childcare